A Precise, Controllable in vitro Model for Diffuse Axonal Injury Through Uniaxial Stretch Injury - Li, Yu; Li, Chaoxi; Gan, Chao; Zhao, Kai; Chen, Jianbin; Song, Jinning; Lei, Ting (Frontiers in Neuroscience, 2019)
Regarding the determination of the biomechanical parameters in a reliable in vitro cell model for diffuse axonal injury (DAI), our study aimed to demonstrate connections between those parameters and secondary axotomy through examination of morphological alterations under a variety of traumatic conditions. In vitro cell model for DAI was established in primary cultured mouse neurons by uniaxial mechanical stretching of nonmyelinated axons under various traumatic conditions as follows: strain (ε) = 5%, 10%, 20% and 50%; strain time (t) = 500 ms, 100 ms and 20 ms; strain rate ranging between 0.1 ~ 25 s-1. Axonal real strains (Strainaxon) were measured as 4.53 ± 0. 27%, 9.02 ± 0. 91%, 17.75 ± 1.65% and 41.8 ± 4.4%, respectively. Axonal real strain rates (SRaxon) ranged between 0.096 ± 0.0054 ~ 20.9 ± 2.2 s-1. Results showed there was no obvious abnormality of axons with a lower strain condition (Strainaxon < 17.75 ± 1.65%) during the acute phase within 30 minutes after injury. In contrast, acute axonal degeneration (AAD) was observed in the axons following injury with a higher strain condition (SRaxon > 17.75 ± 1.65%). In addition, the incidence and degree of AAD were closely correlated with strain rate. Specifically, AAD occurred to all axons that examined, when ε = 50% (strainaxon = 41.8 ± 4.4%) for 20 ms, while no spontaneous rupture was observed in those axons. Besides, the concentration of Ca2+ within the axonal process was significantly increased under such traumatic conditions. Moreover, the continuity of axon cytoskeleton was interrupted, eventually resulting in neuronal death during subacute stage following injury. In this study, we found that there is a minimum strain threshold for the occurrence of AAD in nonmyelinated axons of primary cultured mouse neurons, which ranges between 9.02 ± 0. 91% ~ 17.75 ± 1.65%. Basically, the severity of axonal secondary axotomy post DAI is strain-rate dependent under a higher strain above the threshold. Hence a reliable and reproducible in vitro cell model for DAI was established, when ε = 50% (strainaxon = 41.8 ± 4.4%) for 20 ms.